Imaginative pedagogical approaches in nursing education: moving beyond traditional teaching methods - Muruganandan, N.; B. S., Chethan; Abi Rami, M.; Sharma, Tania; C., Srilatha; C. V., Siji; Umar, Mohammed; K., Lakshimi; Prabha, N.; Katiyar, Jyoti (International Journal of Research in Medical Sciences, 2026)
Nursing education is undergoing a paradigm shift in response to increasing healthcare complexity, rapid technological advancement, and evolving expectations of professional competence. Traditional teacher-centred instructional models are increasingly insufficient to prepare nursing graduates for contemporary clinical practice. This review synthesises current evidence on imaginative pedagogical approaches that move beyond conventional teaching methods in nursing education. A comprehensive literature search was conducted across major electronic databases, and studies were systematically screened using PRISMA guidelines, resulting in the inclusion of 30 eligible studies. The review examines a range of innovative pedagogies, including simulation-based learning, flipped classrooms, virtual and augmented reality, gamification and serious games, problem-and team-based learning, interprofessional education, and competency-based education. Findings consistently demonstrate that these approaches enhance knowledge acquisition, clinical skills, critical thinking, learner engagement, confidence, and readiness for practice when compared with traditional didactic methods. Simulation and flipped learning emerged as the most robustly supported strategies, while immersive digital technologies showed promising but still emerging evidence. Key challenges identified include faculty preparedness, resource constraints, assessment standardisation, and equity of access. The review underscores the need for strategic curricular integration, sustained faculty development, supportive regulatory frameworks, and rigorous evaluation of long-term outcomes. Imaginative pedagogical approaches represent a critical opportunity to strengthen nursing education and align graduate competencies with the demands of modern healthcare systems.